The fundamental architecture of the DCC. (December 2021) - Hackel, Siegfried; Härtig, Frank; Schrader, Thorsten; Scheibner, Alexander; Loewe, Jan; Doering, Lutz; Gloger, Benjamin; Jagieniak, Justin; Hutzschenreuter, Daniel; Söylev-Öktem, Gamze
Abstract: The aim of this publication is to provide an overview of the prototype digital calibration certificate. The role of calibration certificates is explained and the differences between paper-based and digital calibration certificates are described in Section 1. All specifications of the digital calibration certificate are given in Section 2; security aspects are discussed in Section 3; and finally, conclusions are drawn in Section 4. The prototype of the digital calibration certificate (DCC) was first described in the PTB-Mitteilungen [1 ] in 2017.